Evaluation of Regional Elevation and Blade Density Effects on the Efficiency of a 1-kW Wind Turbine for Operation in Low-Wind Counties in Iran - Vahid Akbari; Mohammad Naghashzadegan; Ramin Kouhikamali; Wahiba Yaïci (Wind, 2023)
This research investigates the effect of blade density and elevation above sea level on the startup time (Ts) and power coefficient (Cp) of a 1-kW two-bladed wind turbine. The study uses three Iranian hardwoods as the blade material and four counties of Iran with low wind speeds and different elevations as the case studies. The BW-3 airfoil is considered as the blade profile. A multi-objective optimization process with the aid of the differential evolution (DE) algorithm is utilized to specify the chord length and twist angle. The findings demonstrate that, while the maximum Cp of the optimal blades designed with all three types of wood is high and equal to 0.48, the average Ts of the optimal blades designed with oak and hornbeam wood is 84% and 108% higher than that of alder wood, respectively. It is also observed that, while raising the elevation to 2250 m decreases the Cp by only 2.5%, the ideal blade designed to work at sea level could not manage to start rotating at a height of 1607 m and above. Finally, an improvement in the Ts and Cp was observed by performing optimization based on the local atmospheric conditions associated with the incrementing blade chord length at high elevations.